Effect of Cilostazol and Aspirin During Hyperacute Stroke Phase in Rats: An Experimental Research Study - Christiana Anastasiadou; Anastasios Papapetrou; George Galyfos; Kostas Vekrellis; Patroklos Katafygiotis; Andreas Lazaris; George Geroulakos; Angelos Megalopoulos; Christos Liapis; Nikolaos Kostomitsopoulos; John Kakisis (Neurology International)
Objective: The contralateral hippocampus, a critical region for cognitive function, is often overlooked in everyday clinical practice and stroke research. This study aimed to evaluate the effect of specific antiplatelet agents on the hippocampus (ipsilateral and contralateral) during the hyperacute phase of stroke. Materials and Methods: Twelve-week-old rats were randomly assigned to four groups, each containing six rats: a cilostazol group, an aspirin group, an aspirin plus cilostazol group, and a control group. Each substance was administered for four weeks. Permanent brain ischemia was induced over 2 h using intraluminal middle cerebral artery occlusion. A neurologic examination was conducted, followed by euthanasia and histological examination of the CA1 hippocampal region. The hematoxylin and eosin stain was used to assess the total number of intact neuronal cell bodies and pyknotic nuclei, an indicator of early irreversible neuronal injury. Results: In the ipsilateral hippocampus, monotherapy with either aspirin or cilostazol significantly reduced pyknotic nuclei compared with the control group (p = 0.0016 and p = 0.0165, respectively). However, combination therapy showed no significant difference from the controls (p = 0.2375). In the contralateral hippocampus, cilostazol monotherapy demonstrated significantly reduced pyknotic nuclei (p = 0.0098), whereas aspirin monotherapy and combination therapy did not (p = 0.1009 and p = 0.9999, respectively). A cumulative analysis of both hemispheres revealed that monotherapy with aspirin or cilostazol markedly reduced injury markers (p = 0.0002 and p = 0.0001, respectively), whereas combined therapy revealed no significant benefit (p = 0.1984). A neurological assessment indicated that the most severe deficits were in the combination therapy group. Conclusions: To the best of our knowledge, this is the first study to compare acute histopathological changes in the affected and unaffected hippocampus after a stroke in a rat model. Dual antiplatelet therapy resulted in worse outcomes (histopathological and neurological) than monotherapy.